A single-dose intranasal immunization with a novel bat influenza A virus-vectored MERS vaccine provides effective protection against lethal MERS-CoV challenge - Lei Shi; Sawrab Roy; Yuekun Lang; Yuhan Wen; William J. Mitchell; Wenyu Yang; Liping Wang; Jialin Zhang; Heidi Liu; John P. Driver; Malik Peiris; Wenjun Ma (mBio)
ABSTRACT The threat to global health security posed by Middle East respiratory syndrome coronavirus (MERS-CoV) and emerging MERS-like coronaviruses highlights the need to develop safe and efficient vaccines. Viral vector vaccines have been shown to be effective and are widely used to prevent various viral diseases because they mimic natural infection and induce a more comprehensive immune response. Herein, we developed a novel bat influenza A virus-based vaccine vector by replacing the open reading frame of either bat influenza hemagglutinin or neuraminidase with that of the hemagglutinin-esterase-fusion gene from influenza D virus, which can infect multiple species, including humans and camels. We then generated a temperature-sensitive, cold-adapted, and attenuated MERS vaccine candidate expressing the clade A MERS-CoV spike S1, referred to as Len_S1, using the developed bat influenza vector and demonstrated its safety and immunogenicity. A single-dose intranasal immunization with Len_S1 protected human dipeptidyl-peptidase-4 (hDPP4) transgenic mice from a lethal MERS-CoV challenge. Notably, a two-dose immunization with Len_S1 completely blocked viral replication and lung damage in challenged mice. Further studies revealed that intranasal immunization with Len_S1 in mice elicited mucosal, humoral, and cellular immune responses. Moreover, sera collected from Len_S1-immunized mice were able to cross-neutralize multiple clades of MERS-CoVs. Collectively, these results indicate that Len_S1 is a safe and effective MERS vaccine that induces a comprehensive immune response and provides cross-protection against diverse clades of MERS-CoVs.IMPORTANCEMiddle East respiratory syndrome coronavirus (MERS-CoV) is an important zoonotic virus with pandemic potential that continues to evolve within dromedary camels. However, no licensed vaccine is currently available. Viral vector-based vaccines represent a promising platform, with demonstrated efficacy in preventing viral diseases. In this study, we developed a bat influenza virus-vectored MERS vaccine, Len_S1, that is safe and immunogenic. Intranasal immunization of human dipeptidyl-peptidase-4 (hDPP4)-transgenic mice with Len_S1 induced humoral, mucosal, and cellular immune responses and provided effective protection against a lethal MERS-CoV challenge. Importantly, sera collected from immunized mice cross-neutralized three distinct clades of MERS-CoVs. Our results indicate that Len_S1 is a promising vaccine candidate with the potential to prevent MERS-CoV infection and mitigate the risk of future epidemics and pandemics.